Analysis of English Teachers' Difficulties in Teaching Listening For Young Learners at Elementary School - Lase, Herni Trisna (Progressive of Cognitive and Ability, 2024)
The goal of this study is to describe the problems faced by English teachers in teaching listening through songs for young learners. This study used descriptive qualitative design as the research design. The samples of this study were two English teachers in elementary schools. The data collection technique used in this research is through structured interviews. As for the results of data collection, researchers found several problems faced by English teachers in teaching listening through songs for young learners. These problems come from those faced by students, facilities at school, and the teachers themselves. These problems include students' psychological factors, namely motivation, students' background knowledge, students' attitudes, students' lack of vocabulary, teaching aids or media, and listening teaching methods